God and the illegal alien: United States immigration law and a theology of politics - Heimburger, Robert W. (Law and christianity, 2018)
"The migration movement of peoples across borders is a concern for many societies today. Millions of men, women, and children crossing borders without documents or overstaying visas are considered "illegal aliens" under federal United States law. While the presence of these migrants runs against the law, many arrive in response to U.S. demand for cheap labor and stay to contribute to community life. This book asks where migrants stand within God's world and how authorities can govern immigration with Christian ethics. The author tracks the emergence of the concept of the illegal alien in federal United States law while exploring Christian ways understanding of belonging, government, and relationships with neighbors. A thought-provoking book that provides a fresh response to the difficult issue of illegal immigration in the United States through the context of Christian theology"--